FOLIAR APPLICATION OF SOME NUTRIENTS EFFECTS ON GROWTH CHARACTERS OF PEACH SEEDLING (Prunus persica var nectaren)CV. CRIMSON BABY . - H., IHSAN M.; M., AMMAR M. (Diyala Agricultural Sciences Journal, 2015)
Afield experiment was conducted during two growing seasons ( 2012 -2013) at Abu Ghraib by using peach seedlings of Crimson Baby cultivar to investigate the response of these seedlings to the foliar application of NPK nutrients. And Magesto nutrient solution . Five types of NPK Fertilizer were used (0، balanced (20:20:20)، high-nitrogen NPK (30:10:10) ، high-phosphorus NPK (10:28:10)، and high-potassium NPK(10:10:28) at 2ml. L-1 and the nutrition solution Magesto at(0،2.5، 5) ml.L-1 ، three times each season، the obtained results indicated that The application of (Magesto at 5 ml.L-1) alone gave the highest increase in all characters in both seasons . leaf area، dry weight percentage ، chlorophyll content. The highest leaf nitrogen percentage obtained from high – nitrogen alone and high nitrogen+Magesto 5ml.L-1treatment ، the single application of high phosphorus NPK and high-phosphorus + Magesto5ml.L1TREATMENT increased carbohydrate and phosphorus percentage. The single application of high potassium NPK and high potassium + Magesto5ml.L1treatment increased leaf potassium percentage in both seasons .